Physiological and Proteomic Analysis of the Rice Mutant cpm2 Suggests a Negative Regulatory Role of Jasmonic Acid in Drought Tolerance - Dhakarey, Rohit; Raorane, Manish L.; Treumann, Achim; Peethambaran, Preshobha K.; Schendel, Rachel R.; Sahi, Vaidurya P.; Hause, Bettina; Bunzel, Mirko; Henry, Amelia; Kohli, Ajay; Riemann, Michael (Frontiers in Plant Science, 2017)
It is widely known that numerous adaptive responses of drought-stressed plants are stimulated by chemical messengers known as phytohormones. Jasmonic acid (JA) is one such kind of phytohormone. But there are very few reports revealing its direct implication in drought related responses or its cross-talk with other phytohormones. In this study, we compared the morpho-physiological traits and the root proteome of a wild type (WT) rice plant with its JA biosynthesis mutant coleoptile photomorphogenesis 2 (cpm2), disrupted in the allene oxide cyclase (AOC) gene, for insights into the role of JA under drought. The mutant had higher stomatal conductance, higher water use efficiency and higher shoot ABA levels under severe drought as compared to the WT. Notably, roots of cpm2 were better developed compared to the WT under both, control and drought stress conditions. Root proteome was analyzed using the Tandem Mass Tag approach to better understand this difference at the molecular level. Expectedly, AOC was unique but notably highly abundant under drought in the WT. Identification of other differentially abundant proteins (DAPs) suggested increased energy metabolism (i.e. increased mobilization of resources) and reactive oxygen species scavenging in cpm2 under drought. Additionally, various proteins involved in secondary metabolism, cell growth and cell wall synthesis were also more abundant in cpm2 roots. Proteome-guided transcript, metabolite and histological analyses provided further insights into the favorable adaptations and responses, most likely orchestrated by the lack of JA, in the cpm2 roots. Our results in cpm2 are discussed in the light of JA crosstalk to other phytohormones. These results together pave the path for understanding the precise role of JA during drought stress in rice.